Impact of hydrotherapy on the quality of life of menopausal women (Research, Society and Development, 2020)
Introduction: The intensity of symptomatic symptoms during the menopause period can directly affect the quality of life of women and physical activity in this phase offers several benefits. Hydrotherapy programs in this population have received little attention and there is a need to establish a protocol for immersion in water. Objective: to analyze the benefits of an aquatic therapeutic exercise program under physical, emotional, psychological and quality of life aspects. Methods: This is a quasi-experimental, comparative, longitudinal study. Menopausal women aged between 45 and 70 years attended at the service at Clinical School of Physiotherapy at the Federal University of Paraíba were included in the study. The hydrotherapy protocol was applied for 90 minutes, twice a week for 9 months. Data collection took place through an initial and final evaluation, using the following instruments: Form with sociodemographic and clinical data; the Kupperman Index; Geriatric Depression Scale and the questionnaire Quality of Life Profile for Chronic Patients (PECVEC). Results: With regard to menopausal symptoms, a significant difference was observed (p=0,008). As for the symptoms of depression, no significant changes were observed (p=0,308). Regarding quality of life, we observed an increase in the score, with a significant difference (p=0,008). Conclusion: The applied hydrotherapy protocol provided an improvement in menopausal symptoms, providing physical and functional benefits, in addition to helping to improve the emotional state and quality of life of women.